Boosting Employee Loyalty at XYZ Consulting: Strategies for Long-Term Commitment - Setiawan, Angga; Hendarman, Achmad Fajar (Journal Integration of Management Studies, 2024)
This study delves into the dynamics of employee retention and organizational culture at XYZ, employing a qualitative thematic analysis of interviews with five HR managers. The research aimed to capture a nuanced understanding of factors influencing employee satisfaction, professional growth, and the overall workplace environment. Key themes identified include employee satisfaction and well-being, professional growth and development, compensation and benefits, work flexibility and patterns, leadership and communication, company policy and culture, and technology and systems. The findings reveal that XYZ's strengths lie in a supportive work environment, clear communication channels, financial stability for employees, flexibility in work arrangements, and a commitment to employee safety and career progression. However, challenges such as high employee turnover, communication gaps in professional development, and the need for more adaptive leadership styles were also highlighted. The study's rigorous approach, incorporating multiple reviews and discussions with supervisory bodies, lends credibility to its findings. Despite its focused scope, the study offers valuable insights for organizations looking to enhance employee retention and satisfaction.